Pemanfaatan Artificial Intelligence Sebagai Model Pendukung E-Learning dalam Pendidikan Islam - Qorimah Qorimah; Rustam Ibrahim (Jurnal Budi Pekerti Agama Islam, 2025)
Implementation Artificial Intelligence as a supporting model for e-learning still faces several challenges. This is due to several aspects, such as concerns about loss spiritual touch, low digital literacy educators, limited technological infrastructure in educational institutions, and so on. On the other hand, the interaction that occurs between students and teachers is an emotional and moral dimension that occurs. The purpose study is to analyze the use AI as supporting model for e-learning in Islamic education. In this study, the method used is descriptive qualitative research. The findings study are (1) Views Islamic education practitioners on Artificial Intelligence, one which is that the existence Artificial Intelligence is not absolute replacement between students and teachers. However, Artificial Intelligence is considered means or tool in understanding learning; (2) The results analysis explain that several AI (Artificial Intelligence) in e-learning in Islamic education have been present in several forms, including increasing access and inclusivity, translating and understanding classical manuscripts, analyzing learning and automatic assessment, material recommendation systems and learning personalization, as well Chatbots and virtual learning assistants; (3) Concept Islamic education is not only oriented towards the transfer knowledge (ta'lim), but also the formation of morals and spirituality (tarbiyah and ta'dib).